Research progress on the development, microstructure and properties of Mo–Re alloys for space nuclear reactors - Wenjun Gao; Jingyi Tuo; Yujun Pan; Xuefei Huang; Hui Wang (Journal of Materials Research and Technology, 2025)
With the gradual deepening of space exploration, the requirements for deep space energy and power propulsion systems have become increasingly stringent. Due to its extremely high energy density, strong environmental adaptability, integration of propulsion and power, as well as high reliability, the space nuclear reactor has emerged as a critical component for deep space exploration missions. Mo–Re alloys demonstrate remarkable irradiation damage resistance, excellent high-temperature performance, and good compatibility with nuclear fuel, becoming important promising candidate materials for cladding and core structural components in space nuclear reactors. This review summarizes the recent domestic and international research progress on Mo–Re alloys though comprehensive analysis of three key aspects: preparation methodologies, mechanical properties, and irradiation resistance. Then the existing challenges associated with Mo–Re alloys are also presented, aiming to provide a reference for the design and research of Mo–Re alloys for space nuclear reactors.